Аналітичні дослідження параметрів роторного диспергатора для створення гомогенних білкових структур - Самойчук, Кирило Олегович; Прісс, Євген Рудольфович; Samoichuk, Kyrylo; Priss, Yevhen (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У машинобудівній галузі харчового обладнання операція надання гомогенної структури після ферментації кисломолочних продуктів є новітнім та перспективним процесом у виробництві кисломолочних продуктів. Для її реалізації запропонована конструкція роторного диспергатора з ротором, що регулюється, який здійснює синусоїдальні коливання вздовж вісі. Наведена кінематична схема та принцип дії машини. Обґрунтовано створення динамічної математичної моделі процесу диспергування в роторному апараті з регульованим ротором, в основі якої лежить класична гідродинаміка. Розроблені алгоритми визначення градієнту швидкості та тиску, напір роторного диспергатора та його конструктивно-кінематичні параметри. Миттєві значення швидкостей і тиску будуть визначати ступінь впливу на білкові структури. Значення швидкостей та тиску можна розрахувати за розробленою у статті аналітичною моделлю. Але ступінь впливу на продукт (що буде визначатись реологічними змінами кисломолочних продуктів) можна буде встановити лише експериментально. /// EN: In modern food technologies, a promising direction is the formation of homogenized protein structures, i.e., the controlled stretching and deformation of protein molecules at the micro- and molecular levels during the production of fermented dairy products. In the field of food machinery engineering, the operation of imparting a homogeneous structure after fermentation of cultured dairy products is a novel and promising process in fermented dairy production. To implement this operation, a rotary disperser design with an adjustable rotor performing sinusoidal oscillations along the axis has been proposed. The kinematic scheme and operating principle of the machine are presented. The development of a dynamic mathematical model of the dispersion process in a rotary apparatus with an adjustable rotor is substantiated; the model is based on classical hydrodynamics. Due to sinusoidal variations in the gap height through which the product passes during dispersion, the impact on the protein structures of fermented dairy products changes significantly (from maximum to minimum). Considering that the rotor rotational speed is constant, the pressure generated by centrifugal rotation of the rotor is also constant. Therefore, the main factor governing the change in product flow velocity is the gap size. The velocity reaches its maximum at the maximum gap opening (due to the maximum flow coefficient of the rotor channels) and its minimum at the smallest gap value. At the same time, the flow rate of the liquid product passing through the working rotor gap is also maximal at the largest opening. Thus, rotor rotation combined with axial oscillatory motion produces pulsations of product volume (velocity and pressure). Their instantaneous values determine the degree of influence on protein structures. The velocity and pressure values can be calculated using the analytical model described above; however, the degree of product modification (determined by rheological changes in fermented dairy products) can only be established experimentally.
Analytical studies of rotary disperser parameters for the formation of homogeneous protein structures
Keywords: роторний диспергатор; обробка білкових структур; консистенція кисломолочних продук- тів; гідродинаміка; rotary disperser; protein structure processing; consistency of fermented dairy products; hydrodynamics